1957
DOI: 10.1021/ie50574a033
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms in Leaching Sulfide Minerals

Abstract: Microorganisms in Leaching Sulfide MineralsHere is a new idea for recovering molybdenum from low grade oresThe discovery of methods for reclaiming metals from low grade ore deposits has become an important problem due to the dwindling supply of high grade ores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

1967
1967
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 3 publications
3
43
0
1
Order By: Relevance
“…According to Leathen et al (1953a) (Colmer and Hinkle 1941), ferric salts (Bryner et al 1954), and precipitate of oxidized iron (Silverman and Lundgren 1959a The infrared spectra of the yellowishbrown deposits (Fig. 1) The X-ray diffractograms (Fig.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Leathen et al (1953a) (Colmer and Hinkle 1941), ferric salts (Bryner et al 1954), and precipitate of oxidized iron (Silverman and Lundgren 1959a The infrared spectra of the yellowishbrown deposits (Fig. 1) The X-ray diffractograms (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Since then numerous investigators have confirmed the significance of these organisms in the biogeochemical leaching of metals from pyrite-containing minerals; metals such as copper (Bryner et al 1954: Razzell and Trussell I963a, b; Sutton and Corrick 1964), molybdenum (Bryner and Anderson 1957), lead (Ehrlich 196l), arsenic (Ehrlich 1963), nickel (Razzeil and Trussell 1963b), uranium (Miller et al 1963; Harrison et al 1966; Duncan and Bruynesteyn l97l), and zinc (Zajic 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Bryner and Anderson [78] demonstrated that molybdenite can be bioleached by autotrophic bacteria. Acidithiobacillus ferrooxidans and T. thiooxidans isolated from drainage from Kennecott's open-pit mine in Bingham Canyon, Utah, USA, were shown to be capable of oxidising molybdenite, but only in the presence of pyrite.…”
Section: Microbiology Of Molybdenum In Mine Wastesmentioning
confidence: 99%
“…28 Aykol et al [21] San Telmo mine, Iberian Pyrite Belt, Spain Cu 1970-1989 Acid mine drainage, leachate, pH 0.16-0. 82 10,400 Sánchez-España et al [7] Antamina mine, Peru Cu-Zn-Mo 2002-present Mine drainage, pH 2.2-8.4, median 7.9 10-13,900 Skierszkan et al [8] Machalí, Cachapoal Province, Chile Cu porphyry 1819-present Tailings impoundment channel water 2670-3900 Smuda et al [9] Nickel Rim mine, Sudbury, Canada Ni-Cu 1953-1958 Tailings pore water <0. 005 Lindsay et al [10] Ylöjärvi mine, Finland Cu-W-As 1943-1966 Tailings pore water 1.28-209 Parviainen et al [11] Greens Creek mine, Alaska, USA Zn-Ag-Pb-Au 1989-1993; 1996-present Vadose zone pore-water; tailings pore-water <5-15; <5-1900 Lindsay et al [10] Sherridon mine, Manitoba, Canada…”
Section: Introductionmentioning
confidence: 99%
“…ferrooxidans [19], a possible biological method for the "economic utilization of low-grade zinc sulphide ores" was proposed [20]. Broader recognition of bacterial roles followed from studies of ARD associated with bituminous coal [21][22][23] and copper mine waste dumps [24][25][26].…”
Section: The Chemistry and Microbiology Of Mineral Dissolutionmentioning
confidence: 99%